Character Education Through an Independent Curriculum - Minsih Minsih; Djalal Fuadi; Nanda Dwi Rohmah (AL-ISHLAH: Jurnal Pendidikan, 2023)
Efforts are being made to overcome the crisis in learning and character education with a flexible curriculum. This is in line with the independent curriculum which allows teachers to provide teaching according to the needs of students. This also applies to character education for students who experience character decline due to the COVID-19 pandemic. Therefore, the purpose of this study is to describe the application of character education through an independent curriculum. . The method used in this research is qualitative research with a case study approach. The subjects of this research are students of Elementary School. The research was conducted by determining the schools that had implemented the Independent Curriculum, then the researchers collected data through documentation, observation and interviews, then the data was processed and analyzed. The results of this study are that there are four character education activities through an independent learning curriculum, namely through intracurricular activities including profiles of Pancasila students who are implanted through learning activities and dimensions that are emphasized according to the needs of students, secondly through extracurricular activities held by schools that are tailored to the interests and interests of students. the ability of students, the three co-curricular activities which include a project to strengthen the profile of Pancasila students which are separate from learning activities, and the fourth is character education through culture in schools.